Grassroots Governance and Development of Economic Infrastructure in Selected Local Government Areas of Rivers State - Edozie-Wali Nkechi (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
The place of local government in Nigeria in terms of socioeconomic infrastructural development has expanded the debate whether a local government should be small or large. This study examined the relationship between grassroots governance and economic infrastructural development in selected local government areas of Rivers State from 2015 to 2025. The study is anchored on the decentralization theory and argued that the development of infrastructures is enhanced when authority, resources, and decision-making are transferred to the local level. The study adopted a mixed-methods research design. 400 respondents were determined using the Taro Yamene formular. Data were collected through the use of questionnaire and interviews; this was complemented with qualitative information from documented sources. Data were analyzed using descriptive statistics and Pearson’s product moment correlation. The findings revealed that respondents generally perceived grassroots governance as weak in facilitating road construction and maintenance, as indicated by a low grand mean of 2.14. This suggested poor road quality, irregular maintenance, delayed project completion, and inequitable distribution of infrastructure, particularly in rural areas. However, correlation analysis showed a strong positive and statistically significant relationship between grassroots governance and roads and streets development (r = 0.768, p < 0.05). This implied that improvements in financial, administrative, and political autonomy at the local level are strongly associated with better road infrastructure outcomes. Qualitative evidence further supported these findings, highlighting challenges such as financial dependency on state governments, administrative bottlenecks, and limited community participation. The study concluded that while grassroots governance possesses the potential to enhance infrastructure development, its effectiveness is constrained by systemic limitations. The study recommends among others that governments both state and local should enhance the strengthening of decentralization and ensuring genuine local government autonomy to improve the essentials for roads and streets development in Rivers State.